2020
DOI: 10.1021/acsaem.0c01542
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of 50% Iodine and Excellent Performance of Dye-Sensitized Solar Cell Enabled by TEMPO Radical Dendrimer–Iodide Dual Redox Systems

Abstract: Detrimental effect of counter electrode corrosion, electrolyte leakage problem, and sublimation of iodine ions affect the performance and stability of dye-sensitized solar cells (DSSCs) based on a liquid redox electrolyte system. TEMPO/TEMPO + is the most desirable one to replace the existing redox couples in liquid electrolyte owing to its rapid and reversible one electron kinetics, high diffusion coefficient, and electrochemical stability. In the present study, a fifth generation polyurethane dendrimer end-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It can balance the tri-iodide generation/recombination and the charge transport at the Pt/electrolyte interface. However, an increase in the volume fraction of SrF 2 to 20 and 30 wt % reduced the dye loading of the photoanode and decreased the dye excitation as well as the tri-iodide generation in the electrolyte. The low dye loading of the SrF 2 /TiO 2 hybrid photoanode leads to reduced dye excitation/charge separation, and the reduction process at the Pt/electrolyte interface gets suppressed. , This was the prospective reason for the high R ct for the SrF 2 /TiO 2 ( %w/w 20/80)-DSSC and SrF 2 /TiO 2 ( %w/w 30/70)-DSSC. The obtained low R ct of control-DSSC and SrF 2 /TiO 2 ( %w/w 10/90)-DSSC was in accordance with the estimated shorter charge transport lifetime (τ t ) of 47.82 and 47.46 μs, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can balance the tri-iodide generation/recombination and the charge transport at the Pt/electrolyte interface. However, an increase in the volume fraction of SrF 2 to 20 and 30 wt % reduced the dye loading of the photoanode and decreased the dye excitation as well as the tri-iodide generation in the electrolyte. The low dye loading of the SrF 2 /TiO 2 hybrid photoanode leads to reduced dye excitation/charge separation, and the reduction process at the Pt/electrolyte interface gets suppressed. , This was the prospective reason for the high R ct for the SrF 2 /TiO 2 ( %w/w 20/80)-DSSC and SrF 2 /TiO 2 ( %w/w 30/70)-DSSC. The obtained low R ct of control-DSSC and SrF 2 /TiO 2 ( %w/w 10/90)-DSSC was in accordance with the estimated shorter charge transport lifetime (τ t ) of 47.82 and 47.46 μs, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…37−40 The low dye loading of the SrF 2 /TiO 2 hybrid photoanode leads to reduced dye excitation/charge separation, and the reduction process at the Pt/electrolyte interface gets suppressed. 41,42 This was the prospective reason for the high R ct for the SrF 2 /TiO 2 (%w/w 20/80)-DSSC and SrF 2 /TiO 2 (%w/w 30/70)-DSSC. The obtained low R ct of control-DSSC and SrF 2 /TiO 2 (%w/w 10/90)-DSSC was in accordance with the estimated shorter charge transport lifetime (τ t ) of 47.82 and 47.46 μs, respectively.…”
Section: Photovoltaic Characterization: J−v Curves and Ipce Measurementsmentioning
confidence: 99%
“…The redox centers (electrolyte group), i.e., TEMPO, can be oxidized and reduced reversibly to play a dual role with the redox mediator. 62 The photovoltaic efficiency can be surged by calibrating the redox structure and corresponding potential of electrolyte. In general, relatively high redox potential yields a lower value of photovoltage, which is of course due to an unwanted side reaction at the interface of photoanode and electrolyte.…”
Section: Functional Electrolyte Photovoltaic Reactions and Redox Pote...mentioning
confidence: 99%
“…Photovoltaic redox reaction imparts electrons to the oxidized photosensitizer and accepts electrons from cathode. The redox centers (electrolyte group), i.e., TEMPO, can be oxidized and reduced reversibly to play a dual role with the redox mediator . The photovoltaic efficiency can be surged by calibrating the redox structure and corresponding potential of electrolyte.…”
Section: Functional Electrolyte Photovoltaic Reactions and Redox Pote...mentioning
confidence: 99%
“…The different I2 concentrations in electrolytes influence the charge transportation and electron recombination dynamics in DSSCs [53]. Ali et al [54] showed that the removal of 50% of I2 from the QSSCs significantly improved both the stability and the PCE of DSSCs. The first I2-free DSSC was reported by Wang et al [55] with a PCE of 5.5%, maintaining about 70% of its initial photonic efficiency after one-month storage.…”
Section: Introductionmentioning
confidence: 99%